Effects of Fiber Orientations on Mechanical Properties of a Carbon Fiber Reinforced Composite Material used in Aircraft Applications - Abed, Khuder; Faris, Saad; Naemah, Iman (Al-Nahrain Journal for Engineering Sciences, 2023)
The purpose of this research is to investigate how the fiber orientation and loading axis of a composite material affect its behavior. Consideration was given to two different fiber-to-matrix ratios in order to improve the mechanical properties. Hand lay-up samples were produced in accordance with ASTM D790 for flexural testing. On UTM, tensile and flexural tests were performed on the sample. The effect of fiber orientation modifies the composites’ mechanical properties. As the fiber orientation increased, the tensile strength of the composite would reduce. This carbon/epoxy composite test demonstrates better strength than those conducted at (30, 5, 60, and 90 degrees). For flexural tests, a three-point bend at 30 degrees demonstrates excellent strength. Utilizing the three-point bend method, the flexural strength and flexural modulus have been determined. The tensile strength, young’s modulus, elongation percentage, maximum load to break the composite, peak load, and flexural strength of single- and double-layered carbon fibers were compared and examined. As the number of layers increased, the adhesion between layers of epoxy and fiber carbon, and glass fiber weakened, causing a decrease in almost all mechanical properties. The fabricated 2024-T3 and epoxy glass fiber had higher fatigue strength than aramid reinforced and lower density than steel alloy utilized in aircraft manufacture.